2019
DOI: 10.1111/tbed.13347
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid substitutions in antigenic region B of hemagglutinin play a critical role in the antigenic drift of subclade 2.3.4.4 highly pathogenic H5NX influenza viruses

Abstract: As one of the important control strategies for highly pathogenic avian influenza (HPAI) in China, vaccination has been implemented compulsively in poultry flocks since 2004. However, the emergence and dominance of the circulating antigenic variants require the update of vaccines periodically. In order to investigate the key molecular sites responsible for the antigenic drift, a total of 13 amino acid positions divergent between clade 2.3.4 H5 viruses and their descendent subclade 2.3.4.4 variants in or around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
(56 reference statements)
1
14
0
Order By: Relevance
“…Glycosylation on HA stem sites mainly functions on maintaining the HA structure (Wagner, Heuer, Wolff, Herwig, & Klenk, 2002;Zhang et al, 2015) or cleavage (Yin et al, 2017), and glycosylation on the head sites mainly influences virus binding affinity (Wang et al, 2009) or assists in escaping from immune detection of antibody (Liao et al, 2010;Zost et al, 2017). Recently, the H5 subtype AIV has drastically evolved and alterations in its glycosylation sites have become increasingly complex (Gu et al, 2019;Hillman et al, 2019;Li et al, 2019;Qu et al, 2019;Wille et al, 2019).…”
mentioning
confidence: 99%
“…Glycosylation on HA stem sites mainly functions on maintaining the HA structure (Wagner, Heuer, Wolff, Herwig, & Klenk, 2002;Zhang et al, 2015) or cleavage (Yin et al, 2017), and glycosylation on the head sites mainly influences virus binding affinity (Wang et al, 2009) or assists in escaping from immune detection of antibody (Liao et al, 2010;Zost et al, 2017). Recently, the H5 subtype AIV has drastically evolved and alterations in its glycosylation sites have become increasingly complex (Gu et al, 2019;Hillman et al, 2019;Li et al, 2019;Qu et al, 2019;Wille et al, 2019).…”
mentioning
confidence: 99%
“…Antigenic characterization of the HA of H9 subtype IAVs showed that the HA, in particular the globular head, is the immunodominant component, similar to what is described for other IAVs subtypes. Interestingly, the HA of the H9 subtype lacks the 130 lateral loop that forms the antigenic site A, which is an important antigenic region in other subtypes, such as H5 or H3 HAs [38,39]. Such a feature results in two antigenic sites that overlap, designated site I and site II [40].…”
Section: H9n2 Avian Influenza Virusesmentioning
confidence: 99%
“…Antigenic characterization of the HA of H9 viruses showed that these viruses, like other IAVs, show an immunodominance mediated by the globular head of the HA. Interestingly, the HA of the H9 subtype lack the 130 lateral loop that forms the antigenic site A in other subtypes, such as H5 or H3 HAs (Li et al 2020, Wiley et al 1981). Such feature results in two antigenic sites that overlap, designated site I and site II (Kaverin et al 2004).…”
Section: H9n2 Avian Influenza Virusesmentioning
confidence: 99%